Nicotine supplementation enhances simulated game performance of archery athletes - Hung, B.-L.; Chen, L.-J.; Chen, Y.-Y.; Ou, J.-B.; Fang, S.-H. (Journal of the International Society of Sports Nutrition, 2021)
Background: Nicotine is beneficial to mood, arousal and cognition in humans. Due to the importance of cognitive functioning for archery athletes, we investigated the effects of nicotine supplementation on the cognitive abilities, heart rate variability (HRV), and sport performance of professional archers.